Rigid registration of untracked freehand 2D ultrasound sweeps to 3D CT of liver tumours - Cifor, Amalia; Risser, Laurent; Heinrich, Mattias P.; Chung, Daniel; Schnabel, Julia A. (Lecture Notes in Computer Science (including subseries Lecture Notes in Artificial Intelligence and Lecture Notes in Bioinformatics), 2013)
We present a rigid registration framework for freehand 2D ultrasound sweeps to 3D CT of liver tumours. The method registers the 2D sweeps in a group-wise manner, without the need for prior 3D ultrasound compounding or probe tracking during acquisition. We first introduce a specific acquisition model to keep the dimension of this problem reasonable. Only seven parameters are indeed required to register the images. These are estimated using simulated annealing optimization of a robust modality-independent similarity measure. The framework contrasts the current methods that rely on tracking devices and phantom calibration, which are often difficult to use routinely in clinical practice. Our results on both synthetic and real data show that the method is well-suited for such ultrasound-CT registration of liver tumours. © 2013 Springer-Verlag.
CRIS-Team Scopus Importer:2023-03-08
Keywords: computed tomography; liver tumour; multimodal; registration; ultrasound